Human and Autologous Adipose-derived Stromal Cells Increase Flap Survival in Rats Independently of Host Immune Response. Issue 2 (February 2018) - Toyserkani, Navid Mohamadpour; Jensen, Charlotte Harken; Andersen, Ditte Caroline; Sheikh, Søren Paludan; Sørensen, Jens Ahm
Abstract : Introduction: There is a rising interest in adipose-derived stromal cells for clinical use; however, it is unknown whether freshly isolated stromal cells (SVF) or culture-expanded cells (ASCs) are more efficacious. We therefore aimed to compare the 2 cellular therapies in an in vivo model of angiogenesis, the ischemic flap in rats, which induces acute ischemia. We also aimed to determine the importance of cell presence and the host immune response. Methods: A total of 96 rats (n = 12 in each group) were used, and in each rat, a caudally based random flap measuring 2 × 7 cm was made. The study was conducted in 3 phases. First, each rat was treated with human SVF cells, human ASCs, or vehicle. Second, each rat was treated with human SVF, human SVF lysate, or vehicle. Finally, each rat was treated with rat (autologous) SVF cells or vehicle. Flap survival, vessel density, and stromal cell retention were evaluated after 7 days. Results: The mean survival rates for SVF treatment regardless of human or autologous origin were significantly increased as compared with the control group. Adipose stem/stromal cell and SVF lysate injection did not increase flap survival. Vessel density was increased for human and rat SVF and human ASC but not for SVF lysate. Human cells were not detected in the flaps after 7 days. Conclusions: Flap survival increased with SVF treatment regardless of human or autologous origin, suggesting that increased flap survival is independent of the host immune response. All cell injections lead to increased vessel density, but it did not necessarily lead to increased flap survival. Further research should elaborate which molecular events make SVF treatment more efficacious than ASC. Abstract : Supplemental digital content is available in the text.